Analysis of investigative skills based on the use of tracker video analysis for 21th century skill - Astian Artiningsih; Sabar Nurohman (Universitas Negeri Yogyakarta, 2019)
This study aims to analyze the investigative skills of Junior High School students upon the use of tracker video analysis for 21th century skill.This reasearch was quasy experimental reasearch using non-randomized pretest-posttest control group design. The population was 8th grade of SMP Negeri 4 Depok in academic year of 2018/2019, which consists of 4 classes with a total of 127 students. The samples consist of 30 students of class VIII A and 30 students of class VIII B, which are selected using cluster sampling technique. The Class VIII A was chosen as the control class, which used powerpoint and video, whereas Class VIII B was prepared as the experiment class, which used Tracker Video Analysis. The instruments used were pretest-posttest questions and observation sheet of investigative skill. The data analysis technique used was t-test. The result of this reasearch shows that the analysis through t-test gives a significance level value of investigative skill of 0.024 (Sig. less than α). This shows that there is an infuence of investigative skill of students upon Tracker Video Analysis.